Finite element analyses for hybrid nanofluid flow between two circular cylinders with multiple heat-conducting obstacles using thermal non-equilibrium permeable medium - Sameh E. Ahmed; M.A. Mansour; Anas A.M. Arafa; M.A.Y. Bakier; Eman F. Mohamed (Alexandria Engineering Journal)
This study addresses the critical need for optimizing heat transfer and fluid flow in porous ring structures, which are essential for various thermal management applications. The aim is to investigate how different parameters such as obstacle length(B), heat source position(D), heat generation coefficient(Q), Hartmann coefficient (Ha), porosity(ε), and Rayleigh coefficient (Ra) affect heat transfer and fluid flow characteristics in a porous ring structure with multiple heat sources. The modeling assumes steady-state conditions, isotropic and homogeneous porous media, and uniform heat generation within the obstacles. Finite Element Method (FEM) simulations were employed to analyze the effects of the aforementioned parameters on streamline distributions, temperature profiles, and heat transfer rates. Remarkably, increasing obstacle length and higher porosity generally enhance heat transfer efficiency, while positioning heat sources closer to the outer boundary and higher Rayleigh numbers lead to reduced heat transfer. The study reveals that, contrary to conventional expectations, various parametric changes consistently result in decreased heat transfer, making the porous ring structure suitable for applications requiring thermal isolation or minimized heat leakage.